Wage Determination under Communism and in Transition : Evidence from Central Europe - Swati Basu; Saul Estrin; Jan Svejnar (Institute for the Study of Labor (IZA), 2004)
Using large firm-level data sets from the Czech Republic, Slovakia, Poland and Hungary, we show that the wage behavior of firms changed considerably as these economies launched their transitions to a market system. We find evidence of worker sharing in their enterprise rents and losses at the end of the communist period in some economies and within a year after the launching of the transition, we find rent sharing in all of them. Using the Czech and Slovak data we show that the state-owned enterprises (SOEs) that existed under communism and survived allow for less worker rent-sharing than other firms. We also test for the presence of a wage curve and with the exception of Slovakia we do not find a significant association between local unemployment and wages. Finally, we do not find significant effects of firm ownership on wages.
Keywords: J41; J30; 330; wages; rent-sharing; transition economies; Lohnbildung; Lohnverhandlungstheorie; Rententheorie; Übergangswirtschaft; Schätzung; Tschechische Republik; Polen; Slowakei; rent-sharing